Factors influencing the economic growth in Benin - Bankole, Krystel (2018)
Benin is a developing and democratic country, which thanks to its strategic location in West Africa, and its human capital, political stability, potential and heritage has several advantages which could help improve its economic condition. Our objective is to determine factors influencing the economic growth of Benin during the year 1991 to 2015.Time series analysis and multiple OLS regressions in Gretl were used to find that foreign direct investment, export of good and services, access to electricity and population growth positively and significantly influence the economic growth. And natural resources, debt and unemployment negatively and significantly influence the economic growth of Benin. However, evidence of the impact of Agriculture and Aid on economic growth were not found. This study suggests that, the government of Benin should focus more on activities that attract foreign direct investment; should continue to promote and boost Export; should make an important and necessary effort to invest into production of electricity, in order to become independent; and to motivate a reasonable growth of the population.